Multiclass wound image classification using an ensemble deep CNN-based classifier. (July 2021) - Rostami, Behrouz; Anisuzzaman, D.M.; Wang, Chuanbo; Gopalakrishnan, Sandeep; Niezgoda, Jeffrey; Yu, Zeyun
Abstract: Acute and chronic wounds are a challenge to healthcare systems around the world and affect many people's lives annually. Wound classification is a key step in wound diagnosis that would help clinicians to identify an optimal treatment procedure. Hence, having a high-performance classifier assists wound specialists to classify wound types with less financial and time costs. Different wound classification methods based on machine learning and deep learning have been proposed in the literature. In this study, we have developed an ensemble Deep Convolutional Neural Network-based classifier to categorize wound images into multiple classes including surgical, diabetic, and venous ulcers. The output classification scores of two classifiers (namely, patch-wise and image-wise) are fed into a Multilayer Perceptron to provide a superior classification performance. A 5-fold cross-validation approach is used to evaluate the proposed method. We obtained maximum and average classification accuracy values of 96.4% and 94.28% for binary and 91.9% and 87.7% for 3-class classification problems. The proposed classifier was compared with some common deep classifiers and showed significantly higher accuracy metrics. We also tested the proposed method on the Medetec wound image dataset, and the accuracy values of 91.2% and 82.9% were obtained for binary and 3-class classifications. The results show that our proposed method can be used effectively as a decision support system in classification of wound images or other related clinical applications. Highlights: Deep Learning-based methods can be used for wound analysis. DCNN-based classifiers help wound specialists to classify the wounds efficiently. Multiclass image-wise classification method was proposed for wound classification. Two image-wise classifiers are combined to generate a superior classifier. High classification performance obtained using an Ensemble DCNN-based classifier.